First report and evidence of multiple origins of diflubenzuron resistance alleles in Culex pipiens mosquito from Cyprus - Mastrantonio, Valentina; Vasquez Christodoulou, Marlen; Notarides, Gregoris; Patsoula, Eleni; Lucchesi, Valentina; Piras, Flavio; Bellini, Romeo; Porretta, Daniele (My University, 2025)
Insecticide resistance is one of the primary problems affecting vector control worldwide. Assessing the occurrence of resistant alleles and understanding their origin across the geographic range of vector species is crucial for effective resistance management. In populations of the mosquito Culex pipiens, point mutations conferring resistance to the insecticide diflubenzuron (DFB) were recently found across the Mediterranean basin. In this study, we investigated the possible occurrence of DFB resistance in Cyprus, where West Nile virus outbreaks have been documented in recent years.
Keywords: Diflubenzuron (DFB); Insect growth regulators; Insecticide resistance; Mosquitoes; Vector control; chitin-synthase